Skull base defect in a patient with ozena undergoing dacryocystorhinostomy - Friedel, Mark E. (OceanSide Publications, Inc., 2011)
Ozena, which is often used interchangeably with atrophic rhinitis or empty nose syndrome, is a progressive and chronically debilitating nasal disease that results in atrophy of the nasal mucosa, nasal crusting, fetor, and destruction of submucosal structures. Although the etiology is not completely understood, infection with Klebsiella ozaenae is widely believed to contribute to the destructive changes. We present a case of a patient with ozena secondary to K. ozaenae with extensive destruction of bony structures of the nasal cavity undergoing elective dacryocystorhinostomy. An extensively thinned skull base secondary to the disease process resulted in an unforeseen complication in which the skull base was entered leading to a cerebrospinal fluid leak. Patients with known history of ozena or atrophic rhinitis often have extensive destruction of the lateral nasal wall and skull base secondary to progression of disease. Submucosal destruction of these bony structures mandates the need for extreme caution when planning on performing endoscopic intervention at or near the skull base. If physical examination or nasal endoscopy is suspicious for atrophic rhinitis or a patient has a known history of infection with K. ozaenae, we recommend preoperative imaging for surgical planning with careful attention to skull base anatomy.